Environmental Processes An International Journal - Tsihrintzis, Vassilios A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Provides review and original articles on topics concerning the various processes taking place in the natural and the anthropogenic environment. Offers a medium for publications contributing to the understanding of environmental processes for providing solutions to environmental problems. Presents articles covering original monitoring data, experimental data, theoretical investigations and mathematical modeling of processes in environmental systems. Environmental Processes covers: processes related to the interactions of the water, air-atmosphere, and soil-sediment environments with the humans and the biosphere; environmental flow processes, hydrodynamics and hydrology; pollutant physical, chemical and biological processes, including pollutant sources and origin, fate, dispersion and degradation, transport, deposition and accumulation, and impacts on human health and environmental quality; interaction processes between the social, cultural, economic and natural environments; evaluation of currently applied and new proposed technologies for pollutant treatment and the protection of the environment; testing of currently used and new proposed monitoring, instrumentation and analysis techniques related to the environmental processes; educational, regulatory, and research needs on environmental processes and protection.
Keywords: Water quality; Water pollution; Environmental sciences; Environmental management; Waste management; Environmental Science and Engineering; Environmental Management; Waste Management/Waste Technology; Water Quality/Water Pollution